Correlation between the intensity of venous reflux in the saphenofemoral junction and morphological changes of the great saphenous vein by duplex scanning in patients with primary varicosis - Morbio, A. P.; Sobreira, Marcone Lima [UNESP]; Rollo, Hamilton Almeida [UNESP] (Edizioni Minerva Medica, 2010)
Aim. One of the major causes of chronic venous disease is venous reflux, the identification and quantification of which are important for diagnosis. Duplex scanning allows for the detection and quantification of reflux in individual veins. Evaluation of the great saphenous vein in primary varicosis is necessary for its preservation. Objective of the study is to evaluate a possible correlation between the intensity of reflux at the saphenofemoral junction, diameter alterations of the incompetent great saphenous vein and the practical effect of such correlation. Also to compare the clinical severity of the CEAP classification with such parameters.Methods. Three hundred limbs were submitted to duplex evaluation of their insufficient saphenous veins. Vein diameter was measured on five different points. Velocity and flow at reflux peak and reflux time were determined. The saphenous vein's diameters were correlated with velocity, flow and time. The three latter parameters and diameters were compared with clinical severity according to CEAP.Results. Correlation was found between the saphenous vein's diameters, velocity and flow. No correlation was observed between time and diameter in the thigh's upper and middle thirds. When comparing diameter, velocity and flow with CEAP clinical severity classification, an association was observed. The correlation between reflux time with clinical severity was weak.Conclusion. Reflux time is a good parameter for identifying the presence of reflux, but not for quantifying it. Velocity and peak flow were better parameters for evaluating reflux intensity as they were correlated with great saphenous vein alterations, and were associated with the disease's clinical severity. [Int Angiol 2010;29:323-30]
Keywords: Varicose veins; Venous insufficiency; Saphenous vein; Ultrasonography, Doppler, Duplex